Peningkatan Kemampuan Manajemen Risiko Pelaku UMKM Sidayu untuk Meningkatan Pengelolaan Bisnis dan Pendapatan - Moh. Jufriyanto; Deny Andesta; Tsaqofi Bintang Muslimah; Dhidu Usrin Yadani; Soffiana Agustin; Said Salim Dahdah; Moch. Nuruddin (Pusat Riset dan Inovasi Nasional, 2024)
Business management management cannot be avoided from risks in the form of pure risks and speculative risks. Risk can be associated with the possibility of losses from unwanted adverse events or unexpected events. The problem of MSMEs, especially in Sidayu District, Gresik Regency, is that many MSME actors have not implemented risk management in their businesses. Therefore, this community service activity is carried out to provide education to Sidayu MSME actors to pay attention to the risks that exist in the process of managing their business. From the results of community service activities, they can implement risk management and improve risk management management in their businesses. With the implementation and improvement, it can be used as a means to improve business management and income.